The Use of Youjigo Vocabulary on Instagram: A Sociolinguistic Analysis of the Account @uuui_ycoo - Kurniawati, Heny (Wistara: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze the use of "youjigo" vocabulary in social media communication, particularly on the Instagram account @uuui_ycoo. "Youjigo" (幼児語) refers to the language used by children in Japan, characterized by simpler vocabulary, syllable repetition, and a cuter or more playful way of pronunciation. Originally a phenomenon associated with children, the use of youjigo has recently gained popularity among adults across various social media platforms, including Instagram. This raises questions about the function, reasons, and impact of using youjigo among adult audiences in online communication. The study employs a qualitative approach with content analysis to identify and categorize the youjigo vocabulary used in various posts on the Instagram account @uuui_ycoo. Data for this research was obtained by classifying the youjigo terms found in these posts. Additionally, the study analyzes the social and cultural reasons behind the use of youjigo by adults on social media, as well as how such vocabulary functions to create emotional closeness and familiarity between the account owner and the audience. The findings indicate that the use of youjigo on the Instagram account @uuui_ycoo is intended to create a more relaxed, friendly, and playful atmosphere in social interactions, evoking positive feelings from the audience. Vocabulary such as “うきうき” (uki uki), “だっこ” (dakko), and “ぴょんぴょん” (pyon pyon) plays a significant role in establishing a sense of closeness and charm. The use of youjigo by adults highlights a new dynamic in Japanese language communication, blurring the lines between child and adult speech. This phenomenon is also influenced by social changes and technological advancements, allowing adults to communicate in a more free and emotional way, in line with current social media trends.